Preexisting Heterotypic Ligand-blocking Antibody Does Not Protect Against Genogroup II Norovirus Episodes in Young Children. Issue 10 (18th July 2022) - Becker-Dreps, Sylvia; Brewer-Jensen, Paul D; González, Fredman; Reyes, Yaoska; Mallory, Michael L; Gutiérrez, Lester; Vielot, Nadja A; Diez-Valcarce, Marta; Vinjé, Jan; Baric, Ralph S; Lindesmith, Lisa C; Bucardo, Filemon
Abstract: A birth cohort design was used to understand whether heterotypic ligand-blocking norovirus antibodies provide cross-protection within the GII genogroup. We found that almost one-half of children who experienced a norovirus GII episode had preexisting antibodies heterotypic to the infecting genotype; therefore, these antibodies did not provide cross-protection. Abstract : Almost one-half of young children who experienced a norovirus GII episode had preexisting ligand-blocking antibodies to other GII genotypes tested (GII.4, GII.12, or GII.17). Our findings show that these heterotypic antibodies did not provide cross-protection within the GII genogroup.